(untitled) (Eurasian Journal of Religious Studies, 2023)
The tarîqa Khalwatiyya founded by al-Sayyid Yahyâ al-Bâkûvî who has played an important role in the religious history of Egypt from its introduction into this country at the end of the XV century until today. The current shaykh of al-Azhar, Ahmad al-Tayyib, belongs to great Khalwatî shaykhs family of Upper Egypt demonstrates the lasting and deep-rooted influence of this tarîqa in Egypt, especially among its Azharî establishment. The Khalwatiyya was introduced into Egypt in two stages, not only two and a half centuries apart, but also in ways that were very different. The first Khalwatîs to arrive in Egypt preceded and followed the Ottoman conquest of the country (1517); they were three disciples of Omar al-Rûshânî (d. 1486), one of Yahyâ al-Bakuvî’s khalîfa who settled in Tabrîz, either sent by their master to Egypt to spread the tarîqa Khalwatiyya or to escape the Safavid invasion. The Khalwatiyya was then linked to the Turkish establishment of Cairo: this would not change until the arrival in the mid XVIII century of a Khalwatî Shaykh from Syria, Mustâfâ al-Bakrî (m. 1749). The initiation by al-Bakrî of an Egyptian scholar, Muhammad al-Hifnî (d. 1767), who would later become shaykh of al-Azhar University, set in motion a spectacular spread of the order among Egyptians throughout the country, with a stronghold along the Nile Valley. This expansion, that would continue far into the XIX century, was so unprecedented that historians of Sufism described it as a revival or renewal of the Khalwatiyya in the Arab world at a time when the order was starting to decline in the Balkans and Anatolia. It is in the context of the creation of a vast empire by the Ottomans that the Khalwatiyya, born in Azerbaijan, became a great Sufi order of the Islamic world and of Egypt in particular. Key words: Khalwatiyya, Sayyid Yahyâ al-Bâkûvî, Mustâfâ al-Bakrî, Sufi, Islamic World